Antibacterial and Antibiofilm Activity Testing of Black Betel Leaves (Piper betle L. var. nigra) Ethanol Extract on Staphylococcus aureus and Pseudomonas aeruginosa Using Microdilution Method - Tasya Hardina Adha; Zullies Ikawati; Sylvia Utami Tunjung Pratiwi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
The use of antibiotics is key to treating infected wounds. However, its effectiveness has begun to decrease due to the high bacterial resistance, which is caused by the phenomenon of biofilm. Therefore, it’s necessary to discover new antibacterial and antibiofilm activity agents that can be used as alternative therapies. This study aims to test the antibacterial and antibiofilm activity of black betel leaves (Piper betle L. var. nigra) ethanol extract. Antibacterial and antibiofilm activity test was conducted using the microdilution method against Staphylococcus aureus and Pseudomonas aeruginosa with concentration variations 4; 2; 1; 0.5; 0.25; and 0.125 mg/mL, also used positive control kanamycin 10 mg/mL and negative control DMSO 1%. The results showed that the black betel leaves ethanol extract had low antibacterial activity with MIC50 > 4 mg/mL for both bacteria and vigorous antibiofilm activity with MBIC50 < 0.125 mg/mL for S. aureus and MBIC = 0.491 mg/mL for P. aeruginosa. The antibacterial activity of the black betel leaves ethanol extract was lower than it’s antibiofilm activity, the antibacterial and antibiofilm activities of the black betel leaves ethanol extract were higher against S. aureus than P. aeruginosa.Keywords: Antibacterial, Antibiofilm, Piper betle L. var. nigra